Argon release, crystallization, morphological and optical changes of ion-beam sputtered Ta2O5 thin films during thermal treatments - A. Paolone; M. Bazzan; G. Favaro; F. Borondics; G. Nemeth; F. Capitani; S. Swaraj; R. Belkhou; R. Flammini; J. Teillon; C. Michel; D. Hofman; et al. (Heliyon)
Mass spectrometry measurements at high temperatures on amorphous Ta2O5, produced by Ion Beam Sputtering (IBS) and widely used for the high reflective coatings of the mirrors of gravitational-wave detectors, detect a release of argon around 1000 K. This process is thermally activated and the corresponding activation energy is 410 ± 60 kJ/mol. X-Ray Diffraction (XRD) measurements indicate that in the same range of temperature the crystallization of tantala takes place. Atomic Force Microscopy (AFM) experiments detect a reduction of the surface roughness in the crystalline phase; domains with typical dimensions of the order of few microns appear in the crystal. While the infrared reflectance and absorption properties measured by scanning near-field optical microscopy (SNOM) are extremely homogeneous in the amorphous state, they become dependent on the crystal domain at high temperatures. Moreover, an absorption band around 960 cm−1 appears only in samples heated in vacuum and not in specimen thermally treated in air.Photoemission electron microscopy (PEEM) experiments support the idea that this infrared absorption band is due to the formation of non-homogeneous and non-stoichiometric oxygen domains.